Sodic land reclamation for livelihood security in Central Indo-Gangetic Plains of Uttar Pradesh - MISHRA, V. K.; JHA, S. K.; ARORA, SANJAY; SINGH, Y. P.; DAMODARAN, T.; VERMA, C. L.; SINGH, A K.; SINGH, C. S.; SINGH, B. P.; MISHRA, A. K. (Journal of Soil and Water Conservation, 2020)
The problem of salt affected soils has been reported from many parts of the world from ancient times. The widespread occurrence of these soils in about 120 countries encompassing all continent poses a serious threat to agricultural production in both irrigated and rainfed areas. Based on FAO/UNESCO Soil Map of the World, a total of 9530 lakh ha covering about 7-8% of the surface are suffering from this problem. India has estimated area 67.3 lakh ha of the salt affected soils out of which 13.7 lakh ha land spread over in Central Indo-Gangetic Plains of Uttar Pradesh. These soils have abundance of sodium carbonate, bicarbonate, chloride and sulphate, which stimulated various kinds of geochemical processes within these soils and promotes poor hydro-physical properties. In the soil profile, the level of native soil organic matter is very less due to its high solubility, decomposability and accessibility within the sodic soils. Holistic management practices using one time gypsum (50% of Gypsum Requirement) ameliorant along with salt tolerant cultivars and locally available inputs like dhaincha (Sesbania sp., pressmud) proved to have a significant impact in improvement of soil health and crop productivity. In Uttar Pradesh 3.61 lakh ha lands had been reclaimed by Bhumi Sudhar Nigam, Lucknow, Uttar Pradesh during 1993-2018 with technological backup of Central Soil Salinity Research Institute. Implementation of these management practices considerably reduced soil pH and increased cropping intensity from baseline of 46 to 185 percent during III phase of reclamation programme. The reclamation program of the salt affected soils helped in the upliftment of the economic status of marginal and small farmers.